The digestive system of the “stick bug” Cladomorphus phyllinus (Phasmida, Phasmatidae): A morphological, physiological and biochemical analysis - Monteiro, Emiliano C. (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2014)
This work presents a detailed morphofunctional study of the digestive system of a phasmid representative, Cladomorphus phyllinus. Cells from anterior midgut exhibit a merocrine secretion, whereas posterior midgut cells show a microapocrine secretion. A complex system of midgut tubules is observed in the posterior midgut which is probably related to the luminal alkalization of this region. Amaranth dye injection into the haemolymph and orally feeding insects with dye indicated that the anterior midgut is water-absorbing, whereas the Malpighian tubules are the main site of water secretion. Thus, a putative counter-current flux of fluid from posterior to anterior midgut may propel enzyme digestive recycling, confirmed by the low rate of enzyme excretion. The foregut and anterior midgut present an acidic pH (5.3 and 5.6, respectively), whereas the posterior midgut is highly alkaline (9.1) which may be related to the digestion of hemicelluloses. Most amylase, trypsin and chymotrypsin activities occur in the foregut and anterior midgut. Maltase is found along the midgut associated with the microvillar glycocalix, while aminopeptidase occurs in the middle and posterior midgut in membrane bound forms. Both amylase and trypsin are secreted mainly by the anterior midgut through an exocytic process as revealed by immunocytochemical data.